Isomerization Reactions in Anionic Mesoionic Carbene‐Borates and Control of Properties and Reactivities in the Resulting CoII Complexes through Agostic Interactions. Issue 1 (17th November 2020) - Stubbe, Jessica; Neuman, Nicolás I.; McLellan, Ross; Sommer, Michael G.; Nößler, Maite; Beerhues, Julia; Mulvey, Robert E.; Sarkar, Biprajit
Abstract: We present herein anionic borate‐based bi‐mesoionic carbene compounds of the 1, 2, 3‐triazol‐4‐ylidene type that undergo C−N isomerization reactions. The isomerized compounds are excellent ligands for Co II  centers. Strong agostic interactions with the "C−H"‐groups of the cyclohexyl substituents result in an unusual low‐spin square planar Co II  complex, which is unreactive towards external substrates. Such agostic interactions are absent in the complex with phenyl substituents on the borate backbone. This complex displays a high‐spin tetrahedral Co II  center, which is reactive towards external substrates including dioxygen. To the best of our knowledge, this is also the first investigation of agostic interactions through single‐crystal EPR spectroscopy. We conclusively show here that the structure and properties of these Co II complexes can be strongly influenced through interactions in the secondary coordination sphere. Additionally, we unravel a unique ligand rearrangement for these classes of anionic mesoionic carbene‐based ligands. Abstract : C−N isomerization reactions on borate‐based anionic bi‐mesoionic carbene ligands are reported. The Co II  complexes with these ligands display geometries, spin states, and reactivities that are controlled by agostic interactions in the secondary coordination sphere.